1996
DOI: 10.1055/s-2007-972802
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Cadence Alters Exercise Hemodynamics

Abstract: mmma Previous studies on cycling cadence have focused on the economy of the cadence. in search of the optimal pedal cadence. The purpose of this study was to determine the hemodynarnic changes associated with varylng pedal cadence at a constant workload. It was hypothesized that increased pedal cadence would enhance the skeletal muscle pump, resulting in elevation of cardiac output. Seven cycllsts were enlisted to cycle at 200 watts at pedal cadences of 70.90 and 110 rpm (random order). Oxygen uptake. heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
3
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 4 publications
6
86
3
5
Order By: Relevance
“…These findings are consistent with those of other studies [11,12,22,23]. Despite decreasing pedal forces the need to stabilize the upper body and the trunk area more at higher frequencies results in increased cardiac stress [24].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are consistent with those of other studies [11,12,22,23]. Despite decreasing pedal forces the need to stabilize the upper body and the trunk area more at higher frequencies results in increased cardiac stress [24].…”
Section: Discussionsupporting
confidence: 91%
“…was also found in previous studies [11][12][13]27]. Furthermore, it is already known that blood lactate increases with higher cadences and work load [28,29].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The demonstration that humans under ␤-AR blockade can increase stroke volume via the Frank-Starling mechanism (while heart rate remains depressed) supports the idea that chronotropic and inotropic stimulation through ␤-ARs are not required for maximal exercise performance (45). Other studies have shown that during exercise, intrinsic mechanisms such as increased venous return enhances diastolic filling and hence cardiac output (46,47) and can be preferentially utilized over heart rate changes in some pathological states to maintain cardiac output (48). Together with our data in genetically altered mice, such results underscore the importance of intrinsic preload and afterload mechanisms and tend to mitigate the requirement for ␤-AR signaling in the adaptive responses to exercise.…”
Section: Discussionmentioning
confidence: 57%